Implementasi Kebijakan Penanggulangan Banjir dI DKI Jakarta 2013-2017 - Gilang Ramdhan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
The flood problem is the long-time housework which is continuously done by the DKI Jakarta Government, to overcome the problem of the flood as the output from the policy of DKI Jakarta Government is the implementation of the flood prevention policy, both short-term, medium-term and long-term programs. In the implementation of the policy there are factors that can hamper and support the success of policy implementation there are communication, resources, bureaucratic or implementing attitude, and organizational structure including bureaucratic workflow. In terms of communication the real obstacle is the government are still difficult to establish communication with intermediary parties as one of the stakeholders. In terms of bureaucratic attitudes emphasized the independence of the apparatus to policy makers who have an important role in the success of policy implementation. In the government organization of DKI Jakarta itself has been applied innovation with the yellow, blue, and orange â€œsoldiersâ€ that can support the success of policy implementation. But unfortunately from DKI government's own policy environment does not yet have the full support of Jakarta DPRD so it can hamper the policies to be published by the executive. The conclusion of this paper is the government of DKI has a scope of problems that must be well compromised and which is still a wedge is the communication aspect, both internal and external so that the implementation of flood prevention policy in Jakarta can run well.